Silicon Valley North a high-tech cluster of innovation and entrepreneurship - Shavinina, Larisa V. (Elsevier, 2004)
The Silicon phenomenon was, is, and will be an extremely important phenomenon in the accelerated technological, scientific, and economic development of countries and regions. Silicon Valley North (SVN) is the high tech capital of Canada, the nations most developed and dynamic technology sector, which includes multiple clusters in telecommunications, software, photonics, and life sciences. It gave birth to many well-known companies such as Corel, JDS Uniphase, Mitel, Newbridge Networks, Nortel Networks, Digital Equipment of Canada, just to mention a few. A lot of literature describes Silicon Valley and Silicon Alley in the US, Silicon Islands in Asia, and so on. Despite the quite evident importance of Silicon Valley North for the regional, national, and international technological development (especially when Nortel Networks and JDS Uniphase became global leaders in their fields and expanded in explosive fashion), this phenomenon is far from being well understood.Because of this, a book on the Canadian Silicon Valley is an exceptionally timely endeavor. Silicon Valley North: A High-Tech Cluster of Innovation and Entrepreneurship is devoted to the multidimensional and multifaceted nature of SVN, its history, current state and future developments. The book offers a broad and deeply thematic analysis of one particular innovative clusterSilicon Valley North. The reader will obtain expert insight into what SVN is all about by acquiring a comprehensive and panoramic picture of SVN within a single book. The reader will develop an accurate sense of what spurs high tech start-up companies in SVN toward their exceptional performances, and how to apply these insights to his or her unique regional context.
Keywords: Electronic industries -- Canada.; Telecommunication equipment industry -- Canada.; Computer industry -- Canada.; elektronické knihy; electronic books